Risiko Pencucian Uang dan Portofolio: Hambatan atau Jembatan bagi Modal Asing? - Isnu Pujarama; Khoirunurrofik Khoirunurrofik (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2026)
Foreign portfolio investment (FPI) is highly sensitive to money laundering risks, which degrade transparency, heighten market volatility, and erode investor confidence. However, existing research on anti-money laundering (AML) regulations primarily focuses on foreign direct investment (FDI) and the banking sector. However, foreign portfolio investment (FPI), being highly liquid and sensitive to governance risks, remains relatively underexplored in the anti-money laundering (AML) literature. Furthermore, cross-country variations in institutional capacity may generate heterogeneous effects, particularly between developed and developing economies. This study examines the linear and non-linear impacts of money laundering risk on FPI using panel data from 104 countries (2012–2021). To address endogeneity and cross-country heterogeneity, we employ a two-step Generalized Method of Moments (GMM) estimator. The findings are expected to provide empirical evidence for policymakers in designing financial supervisory systems that are proportionate and do not inadvertently undermine investment attractiveness. The results indicate that, in developing countries, foreign portfolio investment declines at low levels of money laundering risk up to a certain threshold, but increases once this threshold is exceeded. In developed countries, money laundering risk exhibits a non-linear effect on foreign portfolio investment. These findings suggest that policymakers must design proportionate AML frameworks to mitigate financial crimes without inadvertently stifling capital inflows critical for economic growth.